FEATURES OF ULTRASOUND CHANGES IN WOMEN WITH PREMATURE OVARIAN INSUFFICIENCY - Naimova, N.S.; Karimova, N.N. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
In accordance with the purpose and objectives of this study, we studied patients with premature ovarian insufficiency. The patients of the main group (n=92) were divided into two groups: the first group (n=49) included patients with STUMP who underwent surgery with a decrease in ovarian reserve; the second group (n=43) included patients with STUMP, without surgery, but with a decrease in ovarian reserve. The conducted studies showed that in group 1, 46% of patients had less than 4 follicles in the right ovary, and 54% of patients had more than 3 but less than 6 follicles, while 72.2% of patients had less than 4 follicles in the left ovary and 27.8% had more than 3, but less than 6 follicles.